2018
DOI: 10.1002/2017wr022411
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Estimation Directly From Logging‐While‐Drilling Induced Polarization Data

Abstract: In this study, we present the prediction of permeability from time domain spectral induced polarization (IP) data, measured in boreholes on undisturbed formations using the El‐log logging‐while‐drilling technique. We collected El‐log data and hydraulic properties on unconsolidated Quaternary and Miocene deposits in boreholes at three locations at a field site in Denmark, characterized by different electrical water conductivity and chemistry. The high vertical resolution of the El‐log technique matches the lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…This potential of the IP method for mapping sand/clay structures below the water table has been evaluated in this study through synthetic modelling, but field verifications are needed for fully establishing the IP method for mapping potential flow-paths of contamination below water table. However, it is important to note that the approach presented in Maurya et al (2018a) and Fiandaca et al (2018b) for mapping intrinsic permeability, or its counterpart the hydraulic permeability, could be used in cross-borehole imaging in saturated media, opening the way for quantitative prediction of water flow and contaminant transport. Above the water table, mapping permeability is more difficult because a good estimate of saturation with depth is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential of the IP method for mapping sand/clay structures below the water table has been evaluated in this study through synthetic modelling, but field verifications are needed for fully establishing the IP method for mapping potential flow-paths of contamination below water table. However, it is important to note that the approach presented in Maurya et al (2018a) and Fiandaca et al (2018b) for mapping intrinsic permeability, or its counterpart the hydraulic permeability, could be used in cross-borehole imaging in saturated media, opening the way for quantitative prediction of water flow and contaminant transport. Above the water table, mapping permeability is more difficult because a good estimate of saturation with depth is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Gazoty et al 2012b, Rossi et al 2017), permeability estimation (e.g. Fiandaca et al 2018b, time-lapse monitoring of CO2 injection (e.g. Doetsch et al 2015a and active layer dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fiandaca et al () have shown that the bold-italicm0 and C parameters are strongly correlated in the inversion of IP data, and suggest reparameterization of the Cole‐Cole model to improve parameter resolution, for instance by using the maximum imaginary conductivity σmax as the inversion parameter instead of bold-italicm0. Furthermore, by enforcing the proportionality between σsurf and σsurf of equation at the frequency f=true12πτσ, it is possible to define the Bulk and (maximum) Imaginary Conductivity (BIC) Cole‐Cole reparameterization (Fiandaca et al, ; Maurya et al, ) as follows: bold-italicmbold-italicBbold-italicIbold-italicC= {}|σbulk,σmax , τσ, C …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the changes in the groundwater flow field at the site will have a lower impact on the contaminant mass discharge than the distribution of contaminant concentrations. The recent works of Weller et al (2015), Fiandaca et al (2018b), and Maurya et al (2018), suggest that induced polarization data can reproduce the spatial distribution of hydraulic conductivities. Therefore, it may be possible to generalize the results of this study to more heterogeneous settings.…”
Section: 1029/2017wr021855mentioning
confidence: 99%
See 1 more Smart Citation